Traumatic Flap Complications After Femtosecond LASIK. Issue 5 (15th May 2022) - Leccisotti, Antonio; Fields, Stefania V.; De Bartolo, Giuseppe; Malandrini, Alex
Abstract : Purpose: The purpose of this article was to evaluate the prognosis of traumatic flap dislocation or avulsion in a large series of laser-assisted in situ keratomileusis (LASIK) cases. Methods: Retrospective, consecutive, noncomparative case series analyzes the visual and anatomical results after flap dislocation or avulsion, caused by trauma occurred at least 1 month after LASIK. Results: A total of 37, 315 eyes of 19, 602 patients were reviewed. A traumatic flap complication was observed in 9 eyes of 9 patients, with a maximum interval of 37 months after surgery. Flap dislocation with central full-thickness folds was found in 5 cases; flap lifting and repositioning achieved a full recovery of uncorrected visual acuity. In another case, a partially detached flap was repositioned by a microsponge without lifting; self-limiting localized epithelial ingrowth followed. In 3 eyes, a complete flap avulsion occurred and, after epithelialization, a moderate refractive change was observed, comprised between −0.25 and −1 diopters (D) of spherical equivalent, with astigmatism <1 D; in 1 eye, the resulting myopia was corrected by repeat femtosecond LASIK. Conclusions: Traumatic flap complications after femtosecond LASIK are rare but can occur even in the long term; they have a favorable anatomic and visual prognosis.